Comparative efficacy and acceptability of antidepressants in Parkinson's disease: a network meta-analysis. - Jinling Liu; Jiangchuan Dong; Lei Wang; Ying Su; Peng Yan; Shenggang Sun (PLoS ONE)
Background Depression is a common non-motor symptom in patients with Parkinson's disease (PD). There are many kinds of antidepressants being used, such as tricyclic antidepressants (TCAs), selective serotonin reuptake inhibitors (SSRIs), serotonin and norepinephrine reuptake inhibitors (SNRIs), and Dopamine agonists which are suggested as alternative antidepressants for the treatment of depression in PD. Which one should we choose first? Literatures have shown inconsistent results. Methods We conducted a network meta-analysis of randomized controlled trials to compare the efficacy and acceptability of therapeutic methods for the treatment of depression in Parkinson's disease. Results We used the odds ratios (OR) as effect size firstly and the results indicated no statistical significance between each compared intervention. Then we used the logarithm of the individual odds ratios as effect size. With efficacy of TCAs as the standard of comparison, the degree of incoherence (a measure of how closely the entire network fits together) was small (ω =  4.824827e-05). The logor were: SSRIs -0.69 (95% CI -1.28- -0.10); Pramipexole -0.73 (-1.71- -0.26); Pergolide -1.97 (-3.67- 0.27); SNRIs -0.86 (-1.86- 0.15); Placebo -1.24 (-1.99- -0.50). With Placebo as the standard of comparison, the logor were: TCAs 1.24 (0.50- 1.99); SSRIs 0.55 (-0.03- 1.13); Pramipexole 0.51 (-0.12- 1.15); Pergolide -0.73 (-2.25- 0.80); SNRIs 0.38 (-0.42- 1.19); TCAs, pramipexole, pergolide and SNRIs showed better profile of acceptability, leading to significant fewer discontinuations than that of SSRIs. Conclusions There is insufficient evidence to support antidepressant efficacy for SSRIs, pramipexole, pergolide and SNRIs. TCAs might be the best choice when starting antidepressant treatment in patients of Parkinson's disease because it has the most favorable balance between benefits and acceptability, followed by pramipexole and SNRIs, SSRIs might be the last choice.